Trends of case-fatality rate by acute coronary syndrome in Portugal: Impact of a fast track to the coronary unit - Abreu, D. (2019)
Introduction: Efforts were made to improve management of coronary disease as the fast-track system to the Coronary Unit. We aim to analyse case-fatality rates by acute coronary syndrome in Portugal from 2000 to 2016, mainly the impact of the fast-track system and the proportion of patients that activate the fast-track system. Methods: We analysed monthly acute coronary syndrome case-fatality before and after the implementation of the fast-track system in 2007. Impact of the system was assessed through regression models for interrupted time-series. We calculated annual proportion of fast-track system admissions. Results: After 2007 case-fatality by acute coronary syndrome decreased (β=-1.27, p-value < 0.01). The estimates obtained for ST Elevation Myocardial Infarction suggest a reduction of nearly 86 monthly deaths prevented after 2007. The highest percentage of patients admitted through the fast-track system was 35%. Conclusions: Our results suggest fast-track system may have contributed to a decline in acute coronary syndrome case-fatality. However, more than half of patients were not admitted through the system. This should encourage health authorities to make efforts to ensure compliance.